Push-Pull Forces Influencing Migration: African Immigrant Entrepreneurs in South Africa - Bernard Lama Ngota; Elroy Eugene Smith; Ayanda Pamella Deliwe (Journal of Management and Entrepreneurship Research, 2026)
Objective: This study explores the push-pull forces influencing the migration of African immigrant entrepreneurs to South Africa and their contribution to the host country’s economy. Research Design & Methods: Employing a qualitative research strategy based on an interpretive research paradigm, this research conducted in-depth interviews with 12 purposively sampled African immigrant entrepreneurs (owners/managers). The data was analysed thematically, and segments of related data were linked to existing themes. Findings: The results showed that political instability, economic difficulties, insecurity, and inferior academic credentials in their home nations pushed African immigrant entrepreneurs to immigrate to South Africa. Contrastingly, stable political atmosphere, economic opportunities, family reunion, superior academic qualifications, and easy access to visas pulled African immigrant entrepreneurs to South Africa. The research also revealed that employment discrimination, employment termination, labour exploitations, business opportunities, favourable business environment, and acquired business skills pushed African immigrants to venture into entrepreneurship. Implications & Recommendations: The study yields significant practical implications, suggesting that, policymakers should streamline residential procedures for African immigrant entrepreneurs to support business start-up and investment in South Africa. Government and financial entities should offer accessible financial alternatives and support services tailored to African immigrant-owned businesses. Government should advance policies that support entrepreneurship and business development among immigrant groups. Contribution & Value Added: This study makes an important contribution to the existing body of knowledge on African immigrant entrepreneurship, specifically in the South African context. The study provides a valuable understanding into the push-pull forces influencing African immigrant entrepreneurs’ migration to South Africa and their contribution to the host economy.